Analyzing nonlinear impact of economic growth drivers on CO2 emissions: Designing an SDG framework for India. (January 2021) - Shahbaz, Muhammad; Sharma, Rajesh; Sinha, Avik; Jiao, Zhilun
Abstract: Several Asian countries are facing challenges regarding the accomplishment of the objectives of Sustainable Development Goals (SDGs), and India is facing a similar situation. Following this, this study talks about designing an SDG framework for India, which can be used as a benchmark for other Asian countries. In this pursuit, this study looks into whether per capita income, energy use, trade openness, and oil price have any impact on CO2 emissions between 1980 and 2019. The nonlinear autoregressive distributed lag approach proves that the fluctuations in independent variables have an asymmetric long-term impact on CO2 emissions. The results reveal that the prevailing economic growth pattern in India is environmentally unsustainable, because of its dependence on fossil fuel-based energy consumption and imported crude oil. Import substitution has been identified as one of the first stepping stones to address this issue, and accordingly, a multipronged SDG framework has been designed based on the direct and extended version of the study outcomes. While the Central policy framework shows a way to address SDG 7, SDG 8, SDG 12, and SDG 13, the Tangential policy framework shows the way to sustain the Central policy framework by addressing SDG 4. Highlights: Positive variations in national output significantly intensify CO2 emissions in India. Oil price fluctuations have significantly reduced CO2 emissions in the long run. Energy is a significant source of CO2 emissions. Improvement in trade openness strengthens environmental quality. SDG framework is suggested for India.